Patagonian Literature in the Use of Poscolonial Discourse (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
The literature written in and about Patagonia dates back to the legitimizing discourses of territorial appropriation. The historical-graphic invention of this region begins in the 16th century with Antonio Pigafetta's chronicle entitled First Voyage Around the Globe and continues with the writings of 19th-century travelers, which also claim to have documentary validity and have been used from the political sphere to consolidate the change in social practices, especially with regard to the occupation of spaces (note).